FORMULASI DAN EVALUASI MIKROEMULSI KALIUM DIKLOFENAK - Sari, Suci Wulan; Sutarna, Titta Hartyana; Ngadeni, Achmad (Kartika : Jurnal Ilmiah Farmasi, 2024)
Diclofenac potassium is a anti-inflammatory drug that can treat mild to severe pain. Diclofenac potassium is often used but has low water solubility and high permeability. This research aimed to evaluate the microemulsion formulation containing diclofenac potassium in vitro. The microemulsion was made by mixing Tween 80: Span 80 (9: 1) as a surfactant, oleic acid as the oil phase, and propylene glycol as a co-surfactant. Evaluation of the diclofenac potassium microemulsion formulation included determining diclofenac potassium levels and in vitro release studies carried out using a modified flow-through method from a Franz diffusion cell and samples were measured by UV-visible spectrophotometry. The results showed that the levels of potassium diclofenac in the microemulsion preparation were respectively 1: 102.57%, formula 2: 101.38%, formula 3: 102.15, and the average diffusion rate test of the microemulsion preparation at F1 0.1147mg/cm2 F2 0.1552 mg/cm2 F3 0.1633 mg/cm2 with a permeation percentage of F1 6.5%, F2 8.8%, F3 9.2% for 180 minutes.